Integrative Planning of Post-suburban Growth in the Glatt Valley (Switzerland) - Carr, Constance; McDonough, Evan (Raumforschung und Raumordnung | Spatial Research and Planning, 2018)
This paper addresses conditions of post-suburban urbanisation. Our empirical base is drawn from observations of integration initiatives in the region of the Glatt Valley, a rather undefined area extending from the City of Zurich towards the airport and spreading over a number of small municipalities. Under growth pressure, municipalities are coordinating housing, transportation, and economic activity, and this is generating new post-suburban forms. To understand these processes, qualitative methods were used, relevant documents surveyed, and conversational interviews with actors in the area conducted. A process of infrastructure consolidation was observed, which moved towards integrating functional pathways and optimising capital accumulation, and attracting and catering for business development and high-income earners. To date, the region has proved to be diverse and dynamic, while also furthering certain modes of fragmentation and social stratification. The results reveal post-suburban forms that are place specific and path dependent insofar as they are driven by particular arrangements of governance that emphasise a certain mode of integrative planning. This form of post-suburban growth is also producing new forms of fragmentation.